Internalization of Character Education Based on National Hero Example in Developing Nationalism - Ni Ketut Sari Adnyani; I Wayan Budiarta (Cendekia: Jurnal Pendidikan dan Pembelajaran)
The purpose of this study was to analyze the internalization of character education based on exemplary national heroes in learning citizenship education in elementary schools in Karangasem Regency, Bali. "Character Education through exemplary national heroes, begins with findings in the field, that Citizenship Education learning is cognitive-oriented, does not pay attention to didactic and affective meanings. This study used an experimental design in testing the effectiveness of exemplary-based learning of national heroes on social responsibility attitudes and character of elementary school students. The instruments used to collect data in this study were questionnaires, learning outcomes tests, score inventory, and self-evaluation. The questionnaire was designed to determine the feasibility of exemplary-based instruction from national heroes. The learning outcome test is used to find out the score. Data analysis used multivariate analysis of variance. The results showed that a) learning using the role models of national heroes was better than conventional learning in students' citizenship knowledge, b) learning using the role models of national heroes was better than conventional learning on student social responsibility attitudes, and c) learning using the role models of national heroes was better than conventional learning. Students acquire skills to gather information.